Circulating Endothelial Cells Expressing the Angiogenic Transcription Factor Krüppel‐Like Factor 4 are Decreased in Patients with Coronary Artery Disease. (November 2015) - Czepluch, Frauke S.; Vogler, Melanie; Kuschicke, Hendrik; Meier, Julia; Gogiraju, Rajinikanth; Katschinski, Dörthe M.; Riggert, Joachim; Hasenfuss, Gerd; Schäfer, Katrin
Abstract: Objective: The zinc finger transcription factor KLF4 is known to control diverse EC functions. Methods: The functional role of KLF4 for angiogenesis and its association with CAD was examined in HUVECs and human CECs. Results: In two different angiogenesis assays, siRNA‐mediated KLF4 downregulation impaired HUVEC sprouting and network formation. Conversely, KLF4 overexpression increased HUVEC sprouting and network formation. Similar findings were observed after incubation of HUVECs with CdM from KLF4 cDNA‐transfected cells, suggesting a role of paracrine factors for mediating angiogenic KLF4 effects. In this regard, VEGF expression was increased in KLF4‐overexpressing HUVECs, whereas its expression was reduced in HUVECs transfected with KLF4 siRNA. To examine the relevance of our in vitro findings for human endothelial dysfunction, we analyzed the expression of KLF4 in CECs of patients with stable CAD. Flow cytometry analyses revealed decreased numbers of KLF4‐positive CECs in peripheral blood from CAD patients compared to healthy controls. Conclusions: Our findings suggest that KLF4 may represent a potential biomarker for EC dysfunction. In the future, (therapeutic) modulation of KLF4 may be useful in regulating EC function during vascular disease processes.